Political Intersectionality and Democratic Politics in the European Public Sphere. Issue 1 (March 2014) - Siim, Birte
<x content-type="archive" xml:space="preserve">Abstract</x> The European Union (EU) consists of 27 nation states, and its motto "united in diversity" refers to the right of EU citizens to cross borders and work and live legally in another EU country as well as to the accommodation of national minorities. In spite of this common fate, "diversity" issues have increasingly been associated with conflicts between citizens and noncitizens about integration of new migrant groups. At a time of rising populism in Europe, it is important to assess how major political actors of the European Public Sphere (EPS) articulate issues regarding the intersection of gender and ethnic diversity. To do so, this article draws on the findings from the Eurosphere project, which compares sixteen European countries to investigate the inclusion or exclusion of women and minority groups in the EPS (Siim & Mokre 2013). The Eurosphere project provides timely insight into how key actors representing selected political parties and social movements/NGOs across Europe perceive intersections of gender and ethnic diversity.